Hillock formation on CaF2, A12O3, c-SiO2 and MgO single crystal surfaces by ion impact - From potential energy deposition to electronic energy loss. (July 2015) - Wang, Y Y; Grygiel, C; Monnet, I; Gruber, E; Lebius, H; Ban d'Etat, B; Sun, J R; Zhao, Y T; Wang, Z G; Xiao, G Q; Aumayr, F
Synopsis: For impact of very slow highly charged ions on single crystal surfaces the appearance of hillocks can be linked to a threshold in potential energy while for swift heavy ions a minimum electronic energy loss per unit length is necessary. Recent investigations on CaF2 in the medium energy range bridge the gap between these two extreme cases. These investigations are now extended to other target materials.